'There shouldn't be anything wrong with not knowing': epistemologies in simulation. Issue 10 (16th August 2019) - Ng, Stella L; Kangasjarvi, Emilia; Lorello, Gianni R; Nemoy, Lori; Brydges, Ryan
Abstract : Context: Medical education embraces simulation‐based education (SBE). However, key SBE features purported to support learning, such as learner safety and learning through experience and error, may not align with the dominant culture of medicine, in which portraying confidence and certainty about one's knowledge prevails. Misaligned conceptions about knowledge and learning may produce unintended negative effects, including the suboptimal implementation of SBE, which could consequently compromise SBE and its outcomes. Methods: To uncover the epistemological beliefs of students experiencing SBE, we conducted a theory‐informed analysis of interviews with 24 pre‐clerkship medical students following their participation in an SBE training study. Our analysis borrowed from coding methods common in constructivist grounded theory and used Hofer and Pintrich's four dimensions of epistemology as sensitising concepts. Results: Participants subscribed to a dominant view of knowledge as consisting of concrete facts, derived from external sources. By contrast, they described but did not prioritise a conception of building their own knowledge through different learning experiences. Participants positioned experts (i.e. teaching faculty members) as the ultimate knowledge validators through their presence and feedback. Participants also noted that faculty staff could counter medicine's pressures to perform with certainty and confidence at all times by instead embodying and modelling an authentic appreciation of learning through experiences, errors and discovery. Conclusions: Medicine's tendency to idealise the objective pursuit of singular truths may compromise the purported culture of SBE as a space for learning many wide‐ranging aspects of medicine, including how and when to innovate and deviate from norms. Explicit attempts to bridge the epistemological beliefs of medicine and SBE may better enable the realisation of safe experiential learning. Faculty members are positioned to play key roles in enabling this bridging. Abstract : Simulation‐based education is commonly presented as a safe space for experiential learning, but perhaps that is not always the case? Ng et al. point to cultural influences that challenge this perspective.